(untitled) (American Journal of Multidisciplinary Research and Innovation, 2023)
This study cross-sectionally assessed the literacy status among schools in the Schools Division of Calbayog City. It employed a descriptive cross-sectional research design utilizing the EGRA, CRLA and Phil-IRI reading tools fielded out, developed and adopted as principal research instruments in this study. Results revealed that most Grade level learners yielded a significant decrease in the number of learners that are in full refresher and frustration level from pre-assessment result to mid-assessment results. There was a significant decrease in the number of learners identified with frustration level from pre-assessment result to mid-assessment result. Grades 7-12 did not show significant differences between their pre- and mid-assessment results for PHIL-IRI Filipino and English. Therefore, it is recommended that intensification of these tools and orientation to teachers relative to the conduct of the assessment processes may be instituted in the entire division.